Hubungan Konsep Diri dan Komunikasi Interpersonal Siswa di SMA Negeri 8 Padang - Asrul, Anisa; Netrawati, Netrawati (Consilium, 2021)
There is a phenomenon of students who experience student self-concept problems at SMA N 8 Padang. This is marked by the lack of students' ability to communicate their thoughts, difficulty hearing the opinions of others, friends and teachers who criticize themselves and many students who are passive in class and do not provide responses, opinions, criticisms and suggestions when discussions are in progress. When that happens, many students are unable to make decisions because they do not believe in their abilities, such as the habit of students who often cheat when doing assignments given by the teacher. This research uses a quantitative approach with a descriptive correlational research type. The population of this study amounted to 970 students and a sample of 284 students using a proportional random sampling technique. The instrument in this research is the questionnaire instrument. The data were analyzed using descriptive statistics using the product moment correlations formula with the help of the SPSS version 23 program. The results showed that: (1) Students' self-concepts at SMAN 8 Padang varied, most of them were in the medium category with a percentage of 55.28%. (2) Interpersonal communication of students at SMAN 8 Padang is at various levels, most of them are in the medium category with a percentage of 54.93%. (3) There is a significant positive relationship between Self-Concept and Interpersonal Communication of students at SMA N 8 Padang with an rcount of 0.404 with a significant level of 0.000.